STRATEGI PENGGUNAAN MEDIA DIGITAL DALAM PROMOSI PAKET WISATA DI CV. COREN LOMBOK TRAVEL - Nawa Sheva Komala Devi; Sirajuddin, Sirajuddin; Supardi, Supardi (Bajang Institute, 2024)
This research aims to determine the strategy for using digital media in promoting tour packages at CV. Coren Lombok Travel. The method used is a qualitative method by conducting observations, interviews and documentation with several staff on the trip. Based on the results of research conducted through interviews with the owner of Cv. Coren Lombok Travel highlights the strategy of using digital media in promoting their tour packages. CV. Coren Lombok utilizes various digital media such as websites, social media (Instagram, Facebook, YouTube, TikTok) to promote their tourism products. The use of digital media is considered more economical, practical and targeted for delivering tourism product services